Estimation of Nutritive Value and Protein Degradability of Trifolium Repens and Poa Pratensis as the Dominant Pasture Species, Under Simulated Rotational Grazing - Stojanović Bojan; Simić Aleksandar; Đorđević Nenad; Božičković Aleksa; Davidović Vesna; Ivetić Aleksandra (Contemporary Agriculture, 2022)
A cutting trial was conducted to determine the nutritional value, crude protein (CP) fractions distribution and CP ruminal degradability of white clover (Trifolium repens L.) and Kentucky bluegrass (Poa pratensis L.) as the dominant species of permanent grassland. The legume and grass herbage was obtained in the field experiment carried out on pasture throughout a spring growth season where rotational grazing was simulated using three consecutive cuts, which were compared. The fractionation of CP, according to Cornell Net Carbohydrate and Protein System (CNCPS v6.5), was used to predict protein degradability of the legume and grass forage. A significant (p <0.05) lowering of the CP content in the legume and grass herbage was found, while NDF (neutral detergent fiber) and ADF (acid detergent fiber) significantly increased (p <0.05) as the spring growth season progressed. A significant decrease (p <0.05) of fractions A1 and A2 was noted in the legume and grass herbage, with a significant (p <0.05) increase of CP fractions B2 and C as the vegetation season progressed. A higher rumen degradable protein (RDP) content (p <0.05) of white clover and Kentucky bluegrass herbage was obtained in the first harvest, compared with the second and third one. Significantly larger values (p <0.05) of net energy were observed in the white clover and Kentucky bluegrass forage obtained from the first cut, compared with later regrowths, and white clover was characterized by a higher energy content of 12.4–33.1% (dry matter basis), relative to Kentucky bluegrass.